Robotic, laparoscopic, and open colectomy: a case‐matched comparison from the ACS‐NSQIP. Issue 3 (21st October 2016) - Benlice, Cigdem; Aytac, Erman; Costedio, Meagan; Kessler, Hermann; Abbas, Maher A.; Remzi, Feza H.; Gorgun, Emre
Abstract: Background: This study aimed to compare perioperative outcomes of patients undergoing robotic, laparoscopic, and open colectomy using a procedure‐targeted database. Methods: Retrospective review of patients undergoing elective colectomy in 2013 was conducted using the procedure‐targeted database of the American College of Surgeons National Surgical Quality Improvement Program (ACS‐NSQIP). Robotic, laparoscopic, and open groups were matched (1:1:1) based on age, gender, body mass index, surgical procedure, diagnosis and ASA classification. Demographics, comorbidities, and short‐term (30 day) outcomes were compared. Results: Out of 12 790 patients, 387 fulfilled criteria per group after matching. Univariate comparison showed operating time was longer ( P  < 0.001) and hospital stay was shorter ( P  < 0.001) in the robotic group. Morbidity ( P  < 0.001), superficial SSI ( P  < 0.001), bleeding requiring transfusion ( P  < 0.001), ventilator dependency ( P  = 0.003), and ileus ( P  < 0.001) rates were lower in the robotic group. After adjusting for confounders, outcomes were comparable between the groups except hospital stay which was shorter in the robotic group ( P  < 0.001). Conclusions: ACS‐NSQIP data demonstrated several short‐term advantages of robotic surgery compared with laparoscopic and open surgery.